(untitled) (Journal of the College of Basic Education, 2023)
Objective: The study aims to assess nurses’ knowledge toward neonatal resuscitation and find the relationship between the nurses’ knowledge and their demographic characteristics. Methodology: A descriptive study was carried out in 4 teaching hospitals ( Al-Yarmouk Teaching Hospital, Al-Karama Teaching Hospital, Al-karkh Hospital for Deliver, and Al-Kadhimiyia Teaching Hospital) in Baghdad City from the 12th September 2011 to 22th April 2012. A purposive (Randomly) sample of (40) nurses who are working in the delivery room in these hospital. The data was collected through using constructed questionnaire which comprises (44) items add filled by using interview technique. The reliability of the questionnaire was determined through a pilot study and validity through a panel of experts. The data were analyzed through the application of descriptive statistic frequency, percentage, and the application of inferential statistical procedures, which include Pearson correlation coefficient and chi-square. Results: the finding of the study was indicated that the nurses have inadequate knowledge about neonatal resuscitation in the delivery room. Recommendation: the study recommended that nurses’ knowledge should be improved toward neonatal resuscitation in the delivery room